PENGEMBANGAN COMPANY PROFILE UNTUK MENINGKATKAN BRANDING PT. ARSINDO MULYA TAMA - Matin Akbar Ramadhan; Edy Siswanto; Ahmad Ashifuddin Aqham; Dendy Kurniawan (LPPM Politeknik Pratama Kendal, 2025)
The rapid development of the digital printing industry requires companies to have a strong visual identity and communication strategy to improve competitiveness and brand image. PT Arsindo Mulya Tama needs an informative company profile media to support company branding. This research aims to produce a company profile video as a supporting media for branding. The method used is descriptive qualitative, with data collection techniques through observation, interview, and literature study. The final result is an attractive and professional company profile video, expected to strengthen the company's image, expand the market, and become an effective communication tool in facing the digital era and global competition.